Against Analogy: Why Analogical Arguments in Support of Workplace Democracy Must Necessarily Fail. Issue 1 (1st June 2020) - Frega, Roberto
Abstract: This article asks whether the analogy between state and firm is a promising strategy for promoting workplace democracy and provides a negative answer, explaining why analogical arguments are not a good strategy for justifying workplace democracy. The article contends that the state-firm analogy is misguided for at least three reasons: (1) it is structurally inconclusive, (2) it is based on a category mistake, and (3) it leads us away from the central question we should ask, which is: What would concretely imply, and what is required, in order to democratize the workplace? I begin by offering an interpretation of the state-firm analogy which shows that use of the analogical argument in Dahl's justification of workplace democracy engenders excessive and unnecessary theoretical costs which bear negatively on his conclusion. I then proceed to examine more recent contributions to the debate and show that supporters and critics of the state-firm analogy alike do not advance our understanding of the analogical argument. In the last part of the article I provide a general theoretical explanation of why arguments based on the state-firm analogy are not good candidates for defending workplace democracy.